PERBANDINGAN KINERJA KEUANGAN PT ASTRA OTOPARTS TBK SEBELUM DAN SAAT PANDEMI COVID-19 BERDASARKAN RASIO KEUANGAN DAN ECONOMIC VALUE ADDED (EVA) - kartika, Ayu (Jurnal Aplikasi Perpajakan, 2025)
This study aims to analyze the financial performance of PT Astra Otoparts Tbk, calculated using Financial Ratios and Economic Value Added (EVA), for the 2018-2021 period. The research method used is quantitative descriptive, incorporating library research and documentation. The data used is secondary data obtained indirectly from the company through the IDX website (www.idx.co.id) and the official website of PT Astra Otoparts Tbk (www.astra-otoparts.com). Based on the research results, there was no significant difference in the financial performance of PT Astra Otoparts Tbk before and during the COVID-19 pandemic, using either the financial ratio method or the economic value added method. This is due to the fluctuating nature of the results obtained during the 2018-2021 period. However, the economic value added calculation yielded a positive value, indicating that the company successfully provided added value for the company and its shareholders, increased wealth as expected, and increased the value of the capital invested by shareholders.